Analisis Persepsi Mahasiswa PGSD tentang Mata Kuliah Strategi Pembelajaran (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This study aims to examine the perspectives of students in the Primary School Teacher Education Program (PGSD) who are about to begin the Learning Strategies course. The main focus of this research is to investigate how students view the concept of learning strategies, their experiences with various teaching methods, and their expectations regarding the Learning Strategies course. Information was obtained through questionnaires completed by 84 students during the first session of the course. The results of the analysis show that the majority of students have a fairly good basic understanding of learning strategies, although there are some variations in their preferences regarding the use of technology and certain teaching methods. Problem-Based Learning (PBL) and Project-Based Learning (PjBL) are considered effective by the students, although they still face challenges such as time management and differences in learning styles that pose obstacles. This study recommends that teaching in the Learning Strategies course better integrates technology and takes into account the variety of student learning styles to create a more inclusive learning environment.